a(x+1)(x-1)+b(x-2)(x+1)+(x+1)^2=9x^2-x-10
(x+1)(a(x-1)+b(x-2)+(x+1))=(x+1)(9x-10)
a(x-1)+b(x-2)+x+1=9x-10
Now this equation is much simpler!
(a+b)x-a-2b+x+1=9x-10
(a+b)x-a-2b=8x-11
(a+b-8)x-a-2b-11=0
a+b-8=(a+2b-11)/x
I can't solve it 3 variables and 1 equations means infinite answers so yea.
Since they are similar, you need to find the ratio of similarity (I made up the term, there is probably a correct one that I can’t remember).
If you divide 16/40, you’ll find that that ratio is 2.5. So then you just multiply 16 x 2.5. You’ll get 18.
18 is the length of the top of the trapezoid.
You set 18=2x+4 and solve it algebraically. Subtract 4 from both sides.
14=2x
Divide by 2 and x=7
(You can also check that the ratio is right by 16/18 is the same decimal value as 40/45. You’ll get .88888...)
(3x^2+5x-2)- ((2-x^2+2x+5))
(3x^2+5x-2)- ((7-x^2+2x))
Since no more can be added or broken down
3x^2+5x-2 - 7-x^2+2x
2x^2+7x-9
Unit form: 3 tens
Standard form: 30